Sosialisasi Tingkat Pengetahuan Remaja Terkait Kecukupan Gizi Harian Anak Usia Remaja - Harmoko Harmoko; Heryanus Jesajas; Asmirani Alam; Inggrid Welerubun; Juwaher Makatita; Jecklin Lainsamputy; Barnabas Gairtua; Albertus Sairudy; Risart L. Dolewikou; Arnold Ismael Kewilaa; Agnes Serpiela; Sarah Tersia Sarak (Institut Teknologi dan Bisnis Semarang, 2023)
Indonesia, as a developing country, generally has more people who are active or work primarily as farmers with middle to lower family economic status and low levels of knowledge. In particular, knowledge of the importance of daily nutritional needs is not very good. Increasing knowledge of daily nutritional needs is very necessary in order to make people aware of the importance of adequate nutrition for the development of the next generation. Various nutritional sources that can be used to increase nutritional intake, and have relatively cheap prices and can be reached by all groups. It is common knowledge that livestock products have complete nutritional content and high levels of nutrition. Among the livestock products that have quite high quality at affordable prices are eggs. Eggs can be used as a complementary source of nutrition, because eggs are an animal product that is rich in nutrients and easily digested by the human body. This community service is carried out in high school with the target of students so that they gain knowledge regarding the importance of nutritional needs for their physical and non-physical development. The results of implementing community service at SMK N 7 Southwest Maluku school went well in accordance with the strategy that had been prepared by the service team. The implementation of community service is generally divided into four sessions, namely the pretest session, the session providing service materials, the posttest session, and the awarding session.